Circuit design of continuous homodyne detection for Quantum Key Distribution (QKD) chip - Tan, Jonard Aik Soo (Nanyang Technological University, 2020)
Quantum technology is a prevailing research field for both Physics and Engineering. Recent research has brought about indefinite advantages over its classical electronic counterparts; furthermore, electronic components has seemingly approached a saturated level of performance in recent hardware developments. Over the past decade, multiple research on Quantum Key Distribution has shown the security of channels between two parties and could possibly mean the future of communication. In this paper, a continuous homodyne detector is designed, developed, tested to measure its capabilities. It is a powerful tool that serves as a bridge between quantum and classical field. It is necessary for signal processing in the absence of a quantum computer. This paper will also capture progress of project, problems encountered, evaluation of test results and future works.